Pemberdayaan UMKM “Dhe Irma” Guna Meningkatkan Efisiensi Produksi dan Aspek Keuangan melalui Pengabdian Masyarakat: Empowerment of Dhe Irma's MSMEs to Increase Production Efficiency and Financial Management through Community Service - Nirwana, Nihlatul Qudus Sukma; Wulandari, Indah Apriliana Sari; Hermawan, Sigit; Arista, Sintha Wahyu; Sari, Nilam (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Productive MSMEs can have great potential to progress, mainly if they are well managed. This Community Service (Abdimas) program aims to empower the Dhe Irma MSME to increase production efficiency and financial management. Achieving Sustainable Development Goals (SDGs) No. 8, or "Decent Work and Economic Growth," encourages sustainable, inclusive, and productive economic growth and creates decent and productive jobs for all. The main problems faced by this MSME are the lack of understanding of financial recording and limitations in optimizing the production process, which impact business competitiveness. To overcome these problems, this program is carried out through mentoring methods, training, and providing more efficient production tools. This activity includes training in calculating HPP and optimizing the use of production tools. The implementation method in this community service is planning, implementation, and evaluation by the community service team. The results of this program show an increase in efficiency in the production process and a more structured financial recording system. Before this assistance, Pawon Dhe Irma MSME did not have financial reports, and HPP was not calculated in the sale of its products. However, after this assistance, Dhe Irma MSME has a better understanding of financial management, can make financial reports, can calculate HPP, and can increase its production capacity, which ultimately can strengthen business competitiveness in the market.